2020
DOI: 10.1002/fsn3.1616
|View full text |Cite
|
Sign up to set email alerts
|

Changes in volatile compounds of fermented minced pepper during natural and inoculated fermentation process based on headspace–gas chromatography–ion mobility spectrometry

Abstract: Changes in volatile compounds of fermented minced pepper (FMP) during natural fermentation (NF) and inoculated fermentation (IF) process were analyzed by the headspace–gas chromatography–ion mobility spectrometry (HS‐GC‐IMS). A total of 53 volatile compounds were identified, including 12 esters, 17 aldehydes, 13 alcohols, four ketones, three furans, two acids, one pyrazine, and one ether. Generally, fermentation time played an important role in volatile compounds of FMP. It was found that most esters, aldehyde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
3
16
0
Order By: Relevance
“…The contents of acids and ketones in fermented L. edodes increased by 2.16% and 17.8%, respectively, while the contents of alcohols, aldehydes and phenols decreased by 3.66%, 7.42% and 3.87%, which was similar to the results of Qi et al (2021). This might be attribute to the unstable compounds, aldehydes, which are prone to oxidation reactions to generate acids or alcohols (Chen et al, 2020). The results showed that the decrease or disappearance of acids, ketones, alcohols, phenols and aldehydes as well as the balance of these substances had important effects on the flavor formation of fermented L. edodes.…”
Section: Effects Of Mixed Lab Fermentation On the Flavor Substance Of...supporting
confidence: 74%
“…The contents of acids and ketones in fermented L. edodes increased by 2.16% and 17.8%, respectively, while the contents of alcohols, aldehydes and phenols decreased by 3.66%, 7.42% and 3.87%, which was similar to the results of Qi et al (2021). This might be attribute to the unstable compounds, aldehydes, which are prone to oxidation reactions to generate acids or alcohols (Chen et al, 2020). The results showed that the decrease or disappearance of acids, ketones, alcohols, phenols and aldehydes as well as the balance of these substances had important effects on the flavor formation of fermented L. edodes.…”
Section: Effects Of Mixed Lab Fermentation On the Flavor Substance Of...supporting
confidence: 74%
“…The microflora responsible for fermentation contributes to the aroma by utilizing constituent ingredients of plants to produce enzymes that transform natural compounds into flavor compounds [ 44 ]. Lactic acid bacteria turned the carbohydrates of fermented minced pepper into organic acids and alcohols during the fermentation process, while the organic acids and alcohols could combine with each other to form several esters, such as ethyl acetate, with pineapple flavor [ 45 ]. Lee et al [ 46 ] reported that benzaldehyde, which has a cherry-like aroma, was produced from phenylalanine by Tetagenoccocus halophilus degradation in soy sauce.…”
Section: Resultsmentioning
confidence: 99%
“…Yang found that comparing with fresh tobacco, the content of 3‐methyl‐1‐butanol, furfural, and 5‐methylfurfural increase significantly after mildew (Yang, 2016). Chen et al found that 2‐methylbutanoic acid increase with the improvement in fermentation time of minced pepper (Chen et al., 2020).…”
Section: Resultsmentioning
confidence: 99%